2016
DOI: 10.1071/he15078
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation of health services: enablers and barriers faced by organisations when increasing health promotion capacity

Abstract: Issue addressed: Primary healthcare settings are important providers of health promotion approaches. However, organisational challenges can affect their capacity to deliver these approaches. This review identified the common enablers and barriers health organisations faced and it aimed to explore the experiences health organisations, in particular Aboriginal organisations, had when increasing their health promotion capacity. Methods: A systematic search of peer-reviewed literature was conducted. Articles publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
(132 reference statements)
0
18
0
Order By: Relevance
“…Moreover, current indicators of Aboriginal health care quality do not monitor and report on Aboriginal participation in health care delivery [ 3 ]. Few research studies of Aboriginal health promotion have assessed quality against indicators of best practice; for those that have done this, it is generally reported at a community-, and not health system level [ 10 , 24 ]. Using a structured data extraction tool designed for health promotion quality improvement purposes, this study provided insight into the scope of health promotion and identified gaps in quality which could be used to target system level changes and improve Aboriginal health promotion efforts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, current indicators of Aboriginal health care quality do not monitor and report on Aboriginal participation in health care delivery [ 3 ]. Few research studies of Aboriginal health promotion have assessed quality against indicators of best practice; for those that have done this, it is generally reported at a community-, and not health system level [ 10 , 24 ]. Using a structured data extraction tool designed for health promotion quality improvement purposes, this study provided insight into the scope of health promotion and identified gaps in quality which could be used to target system level changes and improve Aboriginal health promotion efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Health promotion is an ongoing strategic priority of NT Health [ 18 , 22 ] and a core function in models of comprehensive primary health care [ 21 ]. However, in reality, a range of challenges influence health promotion delivery and its success in the NT, including the burden of acute care in Aboriginal communities, high workforce turnover, low stability and acute-oriented, temporary staffing [ 19 , 23 ] together with the availability of information about, and capacity to report on, health promotion quality and effectiveness [ 10 , 23 , 24 ].…”
Section: Study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Other health promotion capacity building projects report access to ongoing specialist support was important to achieving project milestones . However, little has been published on how health promotion capacity has been developed in an ACCHS . As far as we can determine, the report of this project to increase health promotion evaluation capacity in an ACCHS is unique.…”
Section: Discussionmentioning
confidence: 99%
“…The terminology of “factors that help or challenge” appears more compatible with a focus on practice than “barriers and enablers.” The terminology of “barriers and enablers”, particularly “perceived barriers” is often associated with a focus on individual human actors who are deterred from behaving in a health‐promoting way . Recent literature recognises that barriers and enablers can operate at organisational and societal levels, as well as individual level . The focus, however, still appears to be on human intention.…”
Section: Methodsmentioning
confidence: 99%